2010
DOI: 10.1364/oe.18.016096
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 30-fs ultraviolet pulses by four-wave optical parametric chirped pulse amplification

Abstract: We report on the generation of approximately 30-fs ultraviolet pulses with approximately 10 microJ energy by means of four-wave optical parametric chirped pulse amplification in fused silica. The four-wave optical parametric amplifier is pumped by the second-harmonic of the Ti:sapphire laser and is seeded by visible broadband chirped signal pulses. The idler pulses are produced in the ultraviolet by four-wave mixing and are compressed in a medium with normal group velocity dispersion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…11 Chénais et al reported the dependence of the "enhancement ratio," defined as the ratio of the VUV intensity with the vaporization laser on relative to that with the vaporization laser off, as a function of UV, visible, and ablation laser beam pulse energies. 29 We have carried out similar experiments but instead report the relative intensity of the VUV generated as functions of the three input laser pulse energies, shown in Fig. 5.…”
Section: 9 Ev (125 Nm)mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Chénais et al reported the dependence of the "enhancement ratio," defined as the ratio of the VUV intensity with the vaporization laser on relative to that with the vaporization laser off, as a function of UV, visible, and ablation laser beam pulse energies. 29 We have carried out similar experiments but instead report the relative intensity of the VUV generated as functions of the three input laser pulse energies, shown in Fig. 5.…”
Section: 9 Ev (125 Nm)mentioning
confidence: 99%
“…LiF, CaF 2 or fused silica. [28][29][30][31] In these cases, the intersection angle of the input beams were chosen to optimize phase-matching conditions for four-wave mixing. In our experiments, the input wavelength is scanned to optimize phase-matching for a given crossing angle.…”
Section: Introductionmentioning
confidence: 99%
“…This offers an additional degree of freedom in frequency conversion. Indeed, by taking an advantage of this possibility, generation of UV laser harmonics by means of fourwave difference frequency mixing [20] and UV-tunable 30-fs pulses by parametric frequency up-conversion of visible pulses [21] was demonstrated. More recently, a similar technique was applied in the near-IR spectral range, yielding broadly tunable sub-30 fs pulses from fused silica based four-wave optical parametric amplifier [22].…”
Section: Introductionmentioning
confidence: 99%
“…The generation of sub-20-fs DUV pulses using nondegenerate chirped-pulse FWM of the fundamental and SH pulses, produced by a commercial Ti:sapphire amplifier in a bulk material appears more compact and cheaper than the frequency doubling of OPA [6] or FWM with OPA [15] because of the high cost and large setup for an OPA system. It also consumes less pump energy and has a higher conversion efficiency than FWM in hollow fiber or noble gas-filled cells [7][8][9].…”
mentioning
confidence: 99%